Expanding the Potential of Tourism in Indonesia through the Digital and Creative Economy in Concern to Sustainable Development - Henry Kuncoroyekti; Vicki Dwi Purnomo; Benedictus Hestu Cipto Handoyo; Syukron Abdul Kadir (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
Indonesia has always been a country known for its rich resources and large population, but the capacity of the nation is sometimes called into question due to the lack of human welfare, underdeveloped infrastructure and the need for environmental management. First, this article provides an overview of sustainable development. Second, this paper looks at the concept of poverty problems that have been solved or reduced by tourism, the digital economy and the creative economy and their consequences for sustainable development. Third, examples of efforts that have been implemented, successful or not. Fourth, this paper discusses the policy implications of this phenomenon for sustainable development. This paper ends with some of the main issues and possible solutions needed to achieve sustainable development in Indonesia.